PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus pada Apotek Prayogi Surabaya) (Jurnal Bisnis Indonesia, 2022)
The influence of human resources in an organization is increasingly being realized so that humans are seen as the most important asset in the company. The provision of compensation and the creation of a safe and comfortable work environment from the company to employees can affect employee performance to achieve a company goal. This study uses quantitative research where there are two variables, namely compensation and work environment as the independent variable and employee performance as the dependent variable. The purpose of this study was to determine whether compensation and work environment had a significant effect on the performance of the Prayogi Pharmacy Surabaya employees. This research questionnaire was distributed to 60 respondents with simple random sampling technique, namely random sampling. This study uses primary data and data obtained from analysis using multiple linear regression analysis, to examine the variables of compensation and work environment on employee performance. The results showed that compensation had a significant effect on employee performance, the work environment had no significant effect on employee performance, while compensation and the work environment simultaneously had a significant effect on employee performance.  DOI : https://doi.org/10.33005/jbi.v13i1.3073